Gambaran Tingkat Pengetahuan Masyarakat Tentang Obat Kortikosteroid Deksametason Di Apotek Nuur Muhammad Banjarmasin - Nazhipah Isnani; Putri Hayati; Muliyani Muliyani; Muhammad Tahdi (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
Corticosteroids are a group of naturally occurring steroid hormones in humans that are produced by the adrenal cortex. Dexamethasone is the most potent synthetic drug and is a corticosteroid drug that is often used and sought after by the public, because of its ability to treat inflammation and allergies, ten times greater than that of prednisone. This research was conducted using a qualitative descriptive design with prospective data collection. This study uses primary data using a questionnaire. This research method is observational. The sampling technique used is Consecutive sampling, namely by selecting samples that meet the research criteria for a certain period of time so that the number of samples is met. The results of this study obtained as many as 40 respondents. The conclusion of this research as a whole is that the level of public knowledge about the corticosteroid drug dexamethasone at the Nuur Muhammad Banjarmasin pharmacy is included in the fairly good category (77.5%).